Developing Teaching Materials in Reading Aloud for Students in Grade V of State Elementary School - Batubara, Yusmaini Ayu; Harahap, Rosmawati; Kartolo, Rahmat; Sutikno (International Journal of English and Applied Linguistics (IJEAL), 2025)
Reading teaching materials look like a story-based book learning media, which are used to convey learning materials to motivate students in practicing their reading skills aloud. Reading teaching materials entitled "Ayu the Astronaut" are used for fifth grade students at SD Negeri 105418 Sinah Kasih. This research and development aims to (1) determine the process and the level of developing reading teaching materials. This research is an R&D and ADDIE models. The trial subjects in this study were eight students from fifth grade. Data collection techniques used observation, interviews, questionnaires, and tests. This study uses quantitative and qualitative analysis techniques. The results of this research and development are (1) the big book product developed using the ADDIE model has met the criteria as a good learning media and has met the criteria of being very valid and valid with the results of the teacher test getting 89%, and the results of the lecturer test 77.5. So, the product qualification is determined to be very valid and suitable for use. (2) The results of the research on the effectiveness of student responses show a score of 89% with the highest score category, which states that the media is interesting so that learning becomes fun.